Screening and Isolation of Bacillus sp. Producing Thermotolerant Protease from Raw Milk - SANTONG, Kannikar; CHUNGLOK, Warangkana; LERTCANAWANICHAKUL, Monthon; BANGRAK, Phuwadol (Walailak Journal of Science and Technology (WJST), 2011)
Screening and isolation of Bacillus sp. were carried out from raw milk samples using Luria Bertani (LB) supplemented with 2 % skimmed milk as a selective media. Forty-one isolates with a clear zone surrounding a colony were primary selected and identified by using biochemical characteristics, Gram stain, and growth of bacteria at 50 °C. Ten out of 41 isolates showing a clear zone diameter of more than 10 mm were selected and evaluated for the presence of protease activity. BA26 and BA27 gave high levels of protease activity with 12 U/mg protein towards 1.5 % casein at 50 °C for 10 min. Based on the biochemical and physiological characteristics, BA26 and BA27 were classified as Brevibacillus non reactive. However, their 16S rRNA gene sequence showed 99 % identity to that of Bacillus subtilis. The enzymes were more specific to 1 % casein than 1 % gelatin. Moreover, the selected bacteria secreted extracellular protease upon incubation at 50 °C and the enzymes were stable even at high temperatures up to 100 °C and 121 °C. This confirmed that the enzyme protease produced by Bacillus sp. are thermotolerant proteases. Keywords: